Literaturoznawcze i językoznawcze podstawy integracji kształcenia polonistycznego = Literary and Linguistic Elements of Integration of Polish Studies'education - Kurczab, Henryk (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author mentions many arguments which motivate the necessity for interdisciplinary methodological measures in order to integrate theory of literature with linguistics and names the consequences for school education of Polish.
Keywords: język polski - nauczanie; dydaktyka literatury